1988
DOI: 10.1172/jci113665
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the rabbit ileal brush-border Na+/H+ exchanger by an ATP-requiring Ca++/calmodulin-mediated process.

Abstract: Brush-border vesicles purified from rabbit ileal villus cells were used to evaluate how Ca++/calmodulin (CaM) regulates the neutral linked NaCl absorptive process, part of which is a Na+/H+ exchanger. After freezing and thawing to allow incorporation of macromolecules into the vesicles, the effect of Ca++/CaM on brush-border Na+ uptake with an acid inside pH gradient, and on Na+/H+ exchange was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Using these cells we then tested the possible involvement of specific protein kinase-and Ca 2ϩ /calmodulin-mediated pathways in the regulation of folic acid uptake by colonocytes. We focused on pathways that involve protein kinases (PKC and PKA) for which consensus sequences have been shown to exist in the recently cloned folate carriers (13)(14)(15)32) as well as those pathways that have been shown to play an important role in the regulation of uptake of other nutrients by epithelial cells (PTK-and Ca 2ϩ /calmodulin-mediated pathways) (33)(34)(35)(36)(37)(38)(39)(40)(41). When specific modulators of these pathways were used, we found that PKC-mediated pathways had no role in regulating folic acid uptake by NCM460 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these cells we then tested the possible involvement of specific protein kinase-and Ca 2ϩ /calmodulin-mediated pathways in the regulation of folic acid uptake by colonocytes. We focused on pathways that involve protein kinases (PKC and PKA) for which consensus sequences have been shown to exist in the recently cloned folate carriers (13)(14)(15)32) as well as those pathways that have been shown to play an important role in the regulation of uptake of other nutrients by epithelial cells (PTK-and Ca 2ϩ /calmodulin-mediated pathways) (33)(34)(35)(36)(37)(38)(39)(40)(41). When specific modulators of these pathways were used, we found that PKC-mediated pathways had no role in regulating folic acid uptake by NCM460 cells.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on pathways that involve protein kinases for which consensus sequences have been shown to exist in recently cloned folate transporters (namely protein kinase C (PKC) and A (PKA)) (13-15, 31) and on pathways that have been shown to play a role in the regulation of uptake of other nutrients by intestinal and other epithelia (namely, PTK and Ca 2ϩ /calmodulin) (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Regulation Of Folic Acid Uptake In Ncm460 Cells and The Rolementioning
confidence: 99%
“…The final two pellets, control and carbachol treated, were needle homogenized with a 1-ml syringe and 25-gauge needle in the same buffer and the suspensions brought to a protein concentration of 5 (20). Uptake of Na' was measured over 8 s after mixing the membranes with transport buffer, which is during the period when 22Na' uptake, with and without a pH gradient, is linear with time in these vesicles (2 changes occurred in the homogenates. In Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Drugs or hormones which raise cytosol free by affecting the activity ofthe Na+/H' exchanger (2). The regulation by Ca2l is somewhat complex.…”
Section: Introductionmentioning
confidence: 99%
“…Collected pellets (basolateral membrane fraction) were phosphorylated in vitro, using the technique of Ruiz & Arruda (1992), by transient exposure to a hypotonic solution containing 10 mM MgCl 2 , 10 mM KCl and 5 mM Mes/Tris buffer pH 6.8, as well as either 0.8 mM ATP, 8 U l _1 creatine kinase, 8 mM creatine phosphate, 1.2 mM CaCl 2 and 1.2 mM PMA (phosphorylating solution), or 0.8 mM AMP-PNP (nonphosphorylating solution). Creatine kinase and creatine phosphate constitute an ATP-regenerating system, while AMP-PNP is a non-hydrolysable analogue of ATP (Rood et al 1988). The treatment lasted 5 min at 30°C, and this procedure resulted in opening up the vesicles.…”
Section: Protein Kinase C Regulation Of Rat Jejunal Transport Systemsmentioning
confidence: 99%